Tindak Pidana Menjual Barang Kena Cukai Yang Tidak Dilekati Pita Cukai Dalam Perspektif Undang-Undang Nomor 39 tahun 2007 Tentang cukai (Analisis Putusan Nomor 18/Pid.Sus.2020/PN.Mdn) - Charles Jhonson Panjaitan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2022)
The crime of excise stamps is very detrimental and disrupts the balance of the life of the Indonesian people. Excise is a state levy whose main function is to limit the circulation of excisable goods. As a consequence of this function, excise duty contributes to state revenue. The results of the study show that the criminal responsibility for the crime of selling excisable goods that are not attached to excise stamps is based on the decision Number 18/Pid.Sus/2020/PN Mdn, namely that the perpetrators have been legally and convincingly proven guilty of committing the crime of selling excisable goods that are not attached with excise stamps. sentenced to imprisonment for 1 (one) year and 4 (four) months, and a fine of Rp. 25,000,000. a number of fines must be paid and if it is not sufficient then it is replaced with imprisonment for 2 (two) months. Legal considerations of judges in the crime of selling excisable goods that are not attached with excise stamps based on Decision Number 18/Pid.Sus.2020/PN.Mdn is that no justifying or forgiving reason is found which indicates an error regarding the person or the legal subject or other reasons that cause cause the defendants to be released from responsibility for the actions that have been committed. Keywords: Crime, Goods, Excise